1998
DOI: 10.1007/bf02237382
|View full text |Cite
|
Sign up to set email alerts
|

Does laparoscopic vs. Conventional surgery increase exfoliated cancer cells in the peritoneal cavity during resection of colorectal cancer?

Abstract: When performed according to strict oncologic surgical principles, laparoscopic techniques in curative colorectal cancer surgery did not have an increased risk of intraperitoneal cancer cell spillage, compared with conventional techniques. We hope that these results can decrease some of the concerns about tumor cell spillage and seeding during laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 18 publications
2
43
0
2
Order By: Relevance
“…Of note, at least eight publications contained duplicated information [6][7][8][9][10][11][12][13] and were not analyzed further. Several other publications were deemed unfit for analysis because of absence of clinical data [14] , faulty randomization [15] and three other trials because they involved different anastomotic techniques during laparoscopic sigmoidectomy [16] or compared hand-assisted laparoscopy to laparoscopy [17] and differences between gasless laparoscopy and pneumoperitoneum during laparoscopic colectomy [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, at least eight publications contained duplicated information [6][7][8][9][10][11][12][13] and were not analyzed further. Several other publications were deemed unfit for analysis because of absence of clinical data [14] , faulty randomization [15] and three other trials because they involved different anastomotic techniques during laparoscopic sigmoidectomy [16] or compared hand-assisted laparoscopy to laparoscopy [17] and differences between gasless laparoscopy and pneumoperitoneum during laparoscopic colectomy [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Issues regarding the pneumoperitoneum and peritoneal implants have already been addressed and refuted by studies on colorectal cancer. 34 Fear remains that these results would not apply to the different biological behaviour of gastric cancer. In a large retrospective cohort study of 1417 patients treated with LAG for gastric cancer, Song and colleagues 10 reported a 13.4% recurrence for advanced gastric cancer and observed a pattern and timing of recurrence similar to that described after open surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Several in vivo studies have also shown that laparoscopy with carbon dioxide insufflations seems to stimulate the growth of dormant tumor cells into overt liver metastases (Gutt et al, 2001;Kim et al, 2002). However, some studies in colon and gallbladder cancer refuted this risk (Kim et al, 1998;Goetze and Paolucci, 2006). Regard to these results, the possibility of peritoneal or port site seeding of malignant cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%